Tell Me a Story: Socio-Emotional Functioning, Well-Being and Problematic Smartphone Use in Adolescents With Specific Learning Disabilities - Sarti, Daniela; Bettoni, Roberta; Offredi, Ilaria; Tironi, Marta; Lombardi, Elisabetta; Traficante, Daniela; Lorusso, Maria Luisa (Frontiers in Psychology, 2019)
Although Specific Learning Disabilities (SLD) are described as specific difficulties in one or more academic areas, often socio-emotional problems are also reported to be related to well-being and school engagement. Moreover, recent evidence shows that emotional problems and reduced social support predict problematic use of new technologies, such as a smartphone, that can, in turn, increase these problems. In this study, we aimed to investigate socio-emotional functioning and its relation to well-being, school engagement, and problematic smartphone use. Social and emotional skills of 19 adolescents with a diagnosis of SLD and 19 control adolescents were assessed through a narrative test; adolescents were requested to narrate complete stories elicited by pictures representing social situations. Information on well-being and problematic smartphone use were collected through questionnaires. The comparison between groups showed differences in cognitive-social skills, although no significant differences in emotional functioning were found. Additionally, the perception of the social environment as supportive and trustworthy was related to general well-being for both groups, whereas the perception of limits and rules set by the adult world appeared to be related to a decreased investment in learning processes only for the SLD students. Finally, correlation analysis showed that smartphone use was associated with reduced perception of social support and to a decreased ability to understand and solve social situations. These results assert the critical role played by social information processing and social support in terms of well-being in adolescence, and contribute to enhancing knowledge of the mechanisms underlying problematic smartphone use in a clinical sample.